Single-stage augmented fluoroscopic bronchoscopy localization and thoracoscopic resection of small pulmonary nodules in a hybrid operating room. (15th November 2022) - Yang, Shun-Mao; Chung, Wen-Yuan; Ko, Hang-Jang; Chen, Lun-Che; Chang, Ling-Kai; Chang, Hao-Chun; Kuo, Shuenn-Wen; Ho, Ming-Chih
Abstract: OBJECTIVES: Hybrid operating rooms (HOR) have been increasingly used for image-guided lung surgery, and most surgical teams have used percutaneous localization for small pulmonary nodules. We evaluated the feasibility and safety of augmented fluoroscopic bronchoscopy localization under endotracheal tube intubation general anaesthesia followed by thoracoscopic surgery as a single-stage procedure in ab HOR. METHODS: We retrospectively reviewed clinical records of patients who underwent single-stage augmented fluoroscopic bronchoscopy localization under general anaesthesia followed by thoracoscopic surgery in an HOR between August 2020 and March 2022. RESULTS: Single-stage localization and resection were performed for 85 nodules in 74 patients. The median nodule size was 8 mm [interquartile range (IQR), 6–9 mm], and the median distance from the pleural space was 10.9 mm (IQR, 8–20 mm). All nodules were identifiable on cone-beam computed tomography images and marked transbronchially with indigo carmine dye (median markers per lesion: 3); microcoils were placed for deep margins in 16 patients. The median localization time was 30 min (IQR 23–42 min), and the median fluoroscopy duration was 3.3 min (IQR 2.2–5.3 min). The median radiation exposure (expressed as the dose area product) was 4303.6 μGym 2 (IQR 2879.5–6268.7 μGym 2 ). All nodules were successfully marked and resected, and the median global operating room time was 178.5 min (IQR 153.5–204 min). There were no localization-related complications, and the median length of postoperative stay was 1 day (IQR, 1–2 days). CONCLUSIONS: Single-stage augmented fluoroscopic bronchoscopy localization under general anaesthesia followed by thoracoscopic surgery was feasible and safe. Abstract : Lung cancer is the leading cause of cancer-related death worldwide [1].